Increased use of analgesics in midlife women but no association with mental stress: observations from the Prospective Population Study of Women in Gothenburg - Dominique Hange; Gunilla Fernlöf; Cecilia Björkelund; Tove Hedenrud (BMC, 2022)
Abstract Background The study is part of the ongoing Prospective Population Study of Women in Gothenburg, Sweden, initiated in 1968-1969 with the aim of characterising a total population of women who were representative of middle-aged females. The aim of the present study was to investigate the prevalence of actual analgesic use (prescribed and self-medication) and the possible association with perceived mental stress among women aged 38 and 50 years, respectively, in the Population Study of Women. Methods Two different cohorts of population-based samples of 38- and 50-year-old women examined in 2004-2005 and 2016-2017, respectively, were eligible participants. The women were representative for their age cohort at the time of the examinations. Use of medicines and especially analgesics, as well as perceived mental stress, was registered. Changes in medicine use among 38- and 50-year-old women between 2004 and 2005 and 38- and 50-year-old women in 2016-2017 were studied. Data were analysed using logistic regression. Use of analgesics and mental stress were analysed controlling for lifestyle factors, use of other medicines and pain. Results The overall sample size across the time periods was 1,073 individuals. The frequency of analgesic use in 38- and 50-year-old women was about 26% in 2004-2005 and 58% in 2016-2017. 28% of women who reported high mental stress in 2004-2005 used analgesics, compared to 60% in 2016-2017. There were no associations between self-perceived mental stress and the use of analgesics. Conclusion The higher use of analgesics among midlife women in 2016-2017 is in line with global findings and could be due to increased availability in Sweden of over the counter medicines. The impact of mental stress on analgesic use found previously by other researchers was not confirmed. However, medicine use as a potential coping strategy is an important public health issue that needs to be further explored.